STRATEGI CALON LEGISLATIF KOTA PEKANBARU DALAM MERAIH SUARA PADA PEMILIHAN UMUM TAHUN 2009 - Larshen Yunus NK Simamora; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Post April 9, 2009 on previously scheduled to take place on April 5, 2009 agoconstitutemilestone in the political history of modern Indonesia in the context of the implementation of the General Legislative Elections with elected representatives of the people in this case to choose legislators Pekanbaru by using a majority vote system of election at this stage of the Open List Proportional system mechanisms that can provide the same opportunity for anyone who wants to become a legislator has completed the democratic system in the field of institutions - political institutions in Indonesia . In the case of urban society pekanbaru faced with a choice to be able to determine simultaneously choose 45 members legisatif second level of Pekanbaru City Council candidates are available as 618 participants competed the Legislative General Election.In the composition of the increasingly limited, the emotional sentiment - was in fact still a primordial reasons and motives in choosing a figure or figures someone who deserves to be served as a legislator. Seen with the effort as do various strategies held by the Legislative Candidates for their vote and win the competition Legislative General Election in Pekanbaru city in 2009. Strategies used include Dor to Dor Come to Every Home Community, Enabling More Success Team, Open Campaign and others - others. In general, 6people of responden a sample of researchers consisting of 2 persons from each party, candidate 1 wins and 1 defeat candidates from each party are available as three types of political parties.In this study population is all Pekanbaru City Legislative Candidates who competed in the 2009 general election. Researchers used for the determination of respondent Quota Sampling. In order to determine who include members of the research sample should first determine the desired respondent. To know about ways and strategies used by the candidates, researchers looked at the status and background of each candidate. In this sampling investigators decide the number of samples per each - each stratum (membership type) tamap random.In this research, using qualitative research model description. The subjects of this study are candidates of Golkar Party with the principle of nationalism, the principle of Joint Democratic Nationalism - Religious and PDS with religious principle.Screening instrument data used is interviews, documentation and literature searches. The data analysis technique used is a qualitative description. The theory used for the formulation of strategy and motive problems in reaching sound Legislative Candidates in the General Election year 2009 is Theory of Action and the Theory of Social Action of the experts Sociology ie, Max Webber and Talcott Parsons.Keywords: Strategy